The Effect of Deep Breathing with Rosemary Essential Oil on the Sleep Quality of Patients Undergoing Upper Limb Orthopedic Surgery - B Rozgard; E Nasiri-Formi; H Akbari; A Kazemi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: One of the important problems of hospitalized and orthopedic patients is sleep disorders and poor sleep quality. Considering the high rate of orthopedic and trauma operations in Iran and lack of studies in this area, the present study was conducted with the aim of comparing the effect of two methods of deep breathing with and without rosemary essential oil on the sleep quality of patients undergoing upper limb orthopedic surgery. Methods: This clinical trial was conducted on 102 orthopedic surgery candidates in three groups of 34 people. The quality of sleep was checked the night before surgery and 7 days after surgery using the Petersburg Questionnaire. A score of 5 or more means poor sleep quality and less than 5 means good sleep. The group of deep breathing with rosemary used a necklace containing cotton soaked in rosemary essential oil; deep breathing was repeated twice a day and 12 times each time for up to 7 days. The group of deep breathing without rosemary used a necklace containing normal saline and the control group used necklace containing cotton without rosemary and normal saline. Then, the results were checked and compared in the groups. Findings: The demographic characteristics of the three groups were similar. 97.1% of patients in the group of deep breathing with rosemary, 58.8% in deep breathing without rosemary, and 23.5% in the control group had good sleep quality until 7 days after surgery. Two days after the operation, the mean sleep score was 11.24±0.58 in the group of deep breathing with rosemary, 8.78±4.58 in the group of deep breathing without rosemary, and 9.43±0.58 in the control group (p=0.016). The quality of sleep in the group of deep breathing with rosemary was better and significant compared to the group without rosemary and the control group (p=0.027). Conclusion: The results of the study showed that deep breathing with rosemary improves the sleep quality of patients undergoing upper limb orthopedic surgery. Therefore, this complementary method can be used to improve sleep in patients undergoing upper limb orthopedic surgery.